A Right Turn in Diagnosis: Highlighting the Importance of TAPSE in Isolated Right Ventricular Myocardial Infarction - Vasudha Dinesh; Arun A Mohanan; Amaravathi Uthayakumar; Vinodha Chandrashekar (POCUS Journal)
Isolated right ventricular myocardial infarction (RVMI) is a rare but significant clinical entity that can present with atypical findings on a standard electrocardiograph (ECG). We present the case of a 65-year-old man with a history of chronic smoking and alcohol use who presented to the emergency department with acute chest pain. An initial ECG showed ST-segment elevation in lead V1 and depression in leads I, aVL, and V2-V6, which did not meet ST-segment elevation myocardial infarction (STEMI) criteria. A right-sided ECG revealed ST-segment elevation in V3R-V6R, concerning for RVMI. Notably, cardiac point of care ultrasound (POCUS) demonstrated normal left ventricular (LV) function without LV or right ventricular (RV) regional wall motion abnormalities (RWMA). However, tricuspid annular plane systolic excursion (TAPSE) was significantly reduced at 1 cm, indicating RV dysfunction despite the absence of RWMA. This is the first known case report that highlights the importance of TAPSE in assessing RV function in isolated RVMI cases. Early recognition and management are crucial, especially in patients with typical presentations, as prompt treatment can prevent complications. This case underscores the need for emergency physicians to maintain a high index of suspicion for RVMI, particularly in atypical presentations, and to utilize cardiac POCUS as an essential tool for evaluation.